2022
DOI: 10.3390/met12071215
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effects of Multiple Laser Shock Peening Treatments on the Electrochemical Corrosion Performance of Welded 316L Stainless Steel Joints

Abstract: To study the influence of laser shock peening on the electrochemical corrosion resistance of welded 316L stainless steel joints, welded 316L stainless steel joints are treated with different laser shock peening treatments (i.e., one, two, and three times). Our analysis employs electron backscattering diffraction (EBSD), scanning electron microscopy (SEM), X-ray diffraction (XRD), an X-ray stress meter, and electrochemical corrosion tests to observe and analyze the microstructure, structural composition, residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…The high-cycle fatigue strength of the specimens increased by 19.82%, which was similar to the result of a 26% increase in the fatigue life of TIG-welded pure titanium [71]. Zhou et al [33] investigated multiple LSP treatments on welded joints of 316 L stainless steel, and the introduction of residual stresses improved the pitting resistance of the specimens. NIE et al [72] investigated a double-sided LSP-treated TA15 TIG head to solve the problems of welding penetration depth and fatigue degradation after double-sided welding.…”
Section: Research Progress On Fatigue Resistance Of Thin-walled Weldm...supporting
confidence: 58%
See 1 more Smart Citation
“…The high-cycle fatigue strength of the specimens increased by 19.82%, which was similar to the result of a 26% increase in the fatigue life of TIG-welded pure titanium [71]. Zhou et al [33] investigated multiple LSP treatments on welded joints of 316 L stainless steel, and the introduction of residual stresses improved the pitting resistance of the specimens. NIE et al [72] investigated a double-sided LSP-treated TA15 TIG head to solve the problems of welding penetration depth and fatigue degradation after double-sided welding.…”
Section: Research Progress On Fatigue Resistance Of Thin-walled Weldm...supporting
confidence: 58%
“…The number of laser processing times Multiple shocks affect the residual compressive stress and the depth of action [33,34] This review takes titanium alloy, nickel-based superalloy, and other typical structural component materials as research objects, and engine fan/compressor blades, high-temperature components, thin-walled weldments, and other components with high failure rates as application cases. The research results on the application of LSP on aeroengine components are systematically summarized, focusing on the characteristics of LSP-induced surface nanocrystallization of metal materials, residual stress characteristics, formation principles, thermal stability, fatigue resistance mechanism, and process methods, etc.…”
Section: Lsp Process Parameter Definition the Effect On The Peening P...mentioning
confidence: 99%
“…Till now, many mechanical surface treatment techniques, including shot peening (SP), laser shock peening (LSP), and ultrasonic nanocrystal surface modification (UNSM), deep rolling, have been developed to achieve the surface modification of metallic materials. [ 17–20 ] However, some negative aspects supplied the influence from uneven surface and some microcracks could destroy the surface finish of the sample. [ 19,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The surface current density was reduced by 98.1% and the pitting potential was increased by 89.5%. Numerous studies by scholars have shown that laser shock peening can cause plastic deformation of metal materials [ 11 , 12 ], proliferation of internal dislocations, precipitation and grain refinement [ 13 , 14 , 15 ], and increase the corrosion resistance of materials.…”
Section: Introductionmentioning
confidence: 99%